The effects of transformational leadership on the distinct aspects development of social identity. (January 2013) - Huang, Jyun-Wei
Although transformational leadership (TFL) has been extensively investigated, the mechanism and process by which perceived TFL exerts its influence on followers' social identification development behaviors is relatively unexplored. Accordingly, this study proposes a latent growth model based on social identity theory to address these influences. To test the proposed model, data were collected by surveying 1, 501 employees of R&D departments at Taiwanese IT firms at multiple points in time over a 10-month period. Therein, we found that as employees perceived more TFL at Time 1, they were more likely to show increases in social identification development behaviors over time. Further, increases in social identification development behaviors demonstrate their positive relationship with task performance and organizational citizenship development behaviors over time. My empirical model confirms all of my proposed hypotheses, and these findings highlight that the potential dynamic consequences of organization behaviors can lead to employee career development.